In vitro effect of substrate, temperature and photoperiod on Phakopsora pachyrhizi urediniospore germination and germ tube growth - Blum,Marta Maria Casa (2015)
In vitro experiments were conducted to assess the effects of substrate, temperature and time of exposure to temperature and photoperiod on P. pachyrhizi uredospore germination and germ tube growth. The following substrates were tested: water-agar and soybean leaf extract-agar at different leaf concentrations (0.5, 1.0, 2.0 and 4.0 g of leaves and 15g agar/L water), temperatures (10, 15, 20, 25, 30, and 35oC) and times of exposure (1, 2, 3, 4, 5, 6, 7, and 8 hours) to temperature and 12 different photoperiods. The highest germination and germ tube length was found for the soybean leaf extract agar. Maximum P. pachyrhizi uredospore germination was obtained at 21.8 and 22.3°C, and maximum germ tube growth at 21.4 and 22.1°C. The maximum uredospore germination was found at 6.4 hours exposure, while the maximum germ tube length was obtained at 7.7 h exposure. Regarding photoperiod, the maximum spore germination and the maximum uredospore germ tube length were found in the dark. Neither spore germination nor uredospore germ tube growth was completely inhibited by the exposure to continuous light.